The Potential of Radarsat Imagery for Population Estimation: Riyadh Case - Abdalla Elsadiq Ali; Emad Eddin Abdou Ibrahim; Elshami Mohd Massad (Journal of King Saud University: Engineering Sciences, 2008)
A spaceborne synthetic aperture radar (SAR) image acquired by the Canadian Radarsat-1 system and covering the city of Riyadh was used to investigate the potential of satellite radars for population estimation. Eight districts with population known apriori were utilized for the purpose. A PCI version 10 software was used to delineate district boundaries and to measure their areas in kilometers. A mathematical relationship was then established between area of district in square kilometers and population in thousands using information from four of these districts. The derived equation was then used to compute the population of the remaining districts. Errors in estimated population figures were then computed and averaged. The results showed that high resolution SAR imagery acquired from spaceborne platforms could be used to derive information about population to an accuracy of ±17%. Although this figure is large compared with those obtained from aerial photography (±6% – ±10%), it still points to the fact that when it is impossible or uneconomical to use aerial photography, radar imagery provides rough information about population. This is a worthwhile conclusion in circumstances such as relief operations and studying effects of natural disasters where preliminary information is urgently needed for the sake of taking further remedial actions. Keywords: Population estimation, Radar backscatter, Photointerpretor